2016
DOI: 10.1074/jbc.m116.722488
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domains of Autoimmune Regulator (AIRE) Modulate INS-VNTR Transcription in Human Thymic Epithelial Cells

Abstract: INS-VNTR (insulin-variable number of tandem repeats)and AIRE (autoimmune regulator) have been associated with the modulation of insulin gene expression in thymus, which is essential to induce either insulin tolerance or the development of insulin autoimmunity and type 1 diabetes. We sought to analyze whether each functional domain of AIRE is critical for the activation of INS-VNTR in human thymic epithelial cells. Twelve missense or nonsense mutations in AIRE and two chimeric AIRE constructs were generated. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The INS gene plays a vital role in the process of insulin secretion and metabolism . Evidence suggests that polymorphism in the INS VNTR locus increases the risk of T1D or LADA by affecting the expression of INS in the thymus, thereby resulting in insulin autoimmunity . Therefore, we performed a meta‐analysis of the INS rs689 polymorphism using nine studies to determine its association with LADA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The INS gene plays a vital role in the process of insulin secretion and metabolism . Evidence suggests that polymorphism in the INS VNTR locus increases the risk of T1D or LADA by affecting the expression of INS in the thymus, thereby resulting in insulin autoimmunity . Therefore, we performed a meta‐analysis of the INS rs689 polymorphism using nine studies to determine its association with LADA.…”
Section: Discussionmentioning
confidence: 99%
“…35,44,45 The period of insulin independence in LADA patients could be due to the slower destruction of insulin-producing 46,47 Evidence suggests that polymorphism in the INS VNTR locus increases the risk of T1D or LADA by affecting the expression of INS in the thymus, thereby resulting in insulin autoimmunity. 15,48 Therefore, we performed a meta-analysis of the INS rs689 polymorphism using nine studies to determine its association with LADA. The analysis revealed a significant inverse association between INS and LADA in all genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…15% of the genetic predisposition for developing type 1 diabetes is attributed to the insulin promotor (insulinlinked variable number of tandem repeats INS-VNTR, chromosome 1p5,511p15), the cytotoxic T-Lymphocyte Antigen-4 receptor (CTLA-4, chromosome 2q33), protein tyrosine phosphatase N22 (PTPN2), and the immune signaling regulator (PTPN22, chromosome 1p13) as well as other genes [28,29]. INS-VNTR polymorphism is responsible for the expression of the insulin gene not only in the pancreas, but also thymus [29]. Mutation or polymorphism of the CTLA-4 gene leads to an uncontrolled proliferation response, which can be the cause of autoimmune diseases including type 1 diabetes [30].…”
Section: Pathogenesis Of Autoimmune Diabetesmentioning
confidence: 99%
“…Moreover, Sparks et al identified additional dominant-negative AIRE mutations associated with the modulation of insulin gene expression in thymus which is essential to induce either insulin tolerance or the development of insulin autoimmunity and type 1 diabetes ( 51 ).…”
Section: New Insights Into Aire Mutationsmentioning
confidence: 99%